Empowerment of the Disaster Preparedness Youth Detachment (Den-Resina) Group Based on TITEER as an Internet of Things (IoT) Media in the Kampar River BasinIot) Pada Daerah Aliran Sungai Kampar: Pemberdayaan Kelompok Detasemen Remaja Siaga Bencana (Den-Resina) Berbasis TITEER Sebagai Media Internet of Things (IoT) Pada Daerah Aliran Sungai Kampar - Deswinda, Deswinda; Rahmi Pramulia; Gita Adelia; Candra Saputra (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
Teratak Village is a watershed that is always flooded every year due to the opening of the Koto Panjang hydroelectric power plant gate which causes high water discharge flowing in the Kampar River. The innovative efforts that can be made to overcome this problem are through the Youth empowerment strategy through the formation of the Disaster Preparedness Youth Detachment (Den-Resina) Based on TITEER as an Internet of Things media. The method of implementing the activity is carried out by Empowering the Community through the process of Training and Organizing Community Groups and is implemented through the Push Model Technology Approach process (Technology Transfer Approach). The results of the implementation of the activity showed that 1). The output of the disaster mapping activity determined the flood risk location area in Teratak Village, Rumbio Jaya District, 2). There was an increase in the average value between the pre-test and post-test related to knowledge of flood disaster preparedness and mitigation before and after training on flood disaster preparedness and mitigation, 3). There was an increase in the average value of the dimension of ability in simulating disaster routes, the dimension of the ability to determine the area of ​​the disaster gathering point and the dimension of the flood disaster emergency response simulation 4). There is an intensity of use of TITEER technology in conducting flood disaster simulations in Teratak Village. The outputs produced are Disaster Risk Map, Decree of Disaster Preparedness Youth Detachment Group (Den-Resina), Formation of Den-Reesina Group, Training Activity Report, Activity Implementation Video, TITEER Product Prototype, Publication in Accredited National Journal, TITEER Product IPR Certificate, RiauPos Newspaper Publication, It is expected that the cadres who have been formed will actively carry out the Den-Resina programs that have been prepared to improve disaster preparedness and mitigation capabilities.